HLA alleles and sustained peanut consumption promote IgG4 responses in subjects protected from peanut allergy - Kanchan, Kanika; Grinek, Stepan; Bahnson, Henry T.; Ruczinski, Ingo; Shankar, Gautam; Larson, David; Du Toit, George; Barnes, Kathleen C.; Sampson, Hugh A.; Suarez-Farinas, Mayte; Lack, Gideon; Nepom, Gerald T.; et al. (The Journal of clinical investigation, 2022)
We investigated the interplay between genetics and oral peanut protein exposure in the determination of the immunological response to peanut using the targeted intervention in the LEAP clinical trial. We identified an association between peanut-specific IgG4 and HLA-DQA1*01:02 that was only observed in the presence of sustained oral peanut protein exposure. The association between IgG4 and HLA-DQA1*01:02 was driven by IgG4 specific for the Ara h 2 component. Once peanut consumption ceased, the association between IgG4-specific Ara h 2 and HLA-DQA1*01:02 was attenuated. The association was validated by observing expanded IgG4-specific epitopes in people who carried HLA-DQA1*01:02. Notably, we confirmed the previously reported associations with HLA-DQA1*01:02 and peanut allergy risk in the absence of oral peanut protein exposure. Interaction between HLA and presence or absence of exposure to peanut in an allergen- and epitope-specific manner implicates a mechanism of antigen recognition that is fundamental to driving immune responses related to allergy risk or protection.